Changes of Agricultural Landscape Pattern – Non-Natural Driving Forces Analyzing Based on the North-Western Region Of Poland - Markuszewska, Iwona (Quaestiones Geographicae, 2013)
In this paper, preceding changes and current situation in agricultural landscape pattern were elaborated as well as future transition was discussed. The North-Western Region of Poland was chosen as a study area, however, the research was conducted at the regional level, in provinces of this region including: Lubuskie, Wielkopolskie and Zachodniomomorskie. For analysis statistical data from Common Agricultural Census, containing the last two decades, between 1990-2010, were extracted. Based on established knowledge and proposed approach driving forces of landscape changes were identified. The research deals with the following aspects: 1) identification of underlying trends of landscape changes that took place over the study period, 2) finding driving forces responsible for cause-effect relationships in landscape alteration, 3) recognition of farmers’ reasons for what they took actions leading to landscape changes, and 4) identification of major current and foreseeable future tendencies of modification of landscape pattern. Political, economic and social driving forces, as the most affecting, were recognized and their influence on agricultural landscape structure was analyzed